Effect of Tai Chi Practice on the Adaptation to Sensory and Motor Perturbations While Standing in Older Adults - Arion Dey; Huiyeong Chang; Laila Shaaban; Armaan Suga; Genavieve Braden; Andres Bustamante; Jisang Park; Shenhua Zhang; Yang Hu; Manuel E. Hernandez (Applied Sciences)
Tai Chi provides an age-appropriate exercise to decrease fall risks in older adults. However, the exact mechanism underlying the benefits of Tai Chi practice remains an open question. Thus, this study examined how aging and Tai Chi practice impact adaptation to sensory and motor perturbations while standing. We hypothesized that older Tai Chi practitioners would exhibit a decreased reliance on visual processes as sensory and motor perturbations increased, relative to naive healthy older adults. Using rambling and trembling decompositions of the center of pressure (COP) and frequency-domain features, we examined changes in low (0–0.3 Hz), medium (0.3–1 Hz), and high (1–3 Hz) frequency components, reflecting contributions from the visual, vestibular/somatosensory, and proprioceptive systems, respectively, in healthy young adults (HYA), healthy older adults (HOA), and Tai Chi practicing older adults (TCOA). Our results revealed statistically significant condition-by-group interactions in high-frequency COP-x and rambling-x and COP-y components, medium-frequency COP-y components, and all low-frequency components in COP and trembling (p < 0.05). Further, a significant trial-by-group interaction in high-frequency rambling-y was observed (p < 0.05). These results indicate age and Tai-chi-related differences in modulation of sensory contributions to balance as perturbations increase, and with repeated practice, which merit further investigation.